Coseismic Stress and Strain Field Changes Investigation Through 3‐D Finite Element Modeling of DInSAR and GPS Measurements and Geological/Seismological Data: The L'Aquila (Italy) 2009 Earthquake Case Study. Issue 5 (7th May 2018) - Castaldo, R.; de Nardis, R.; DeNovellis, V.; Ferrarini, F.; Lanari, R.; Lavecchia, G.; Pepe, S.; Solaro, G.; Tizzani, P.
Abstract: We investigate the L'Aquila 2009 earthquake (AQE, M w 6.3, Italy) through a 3‐D Finite Element (FE) mechanical model based on the exploitation of ENVISAT DInSAR and GPS measurements and an independently generated fault model. The proposed approach mainly consists of (a) the generation of a 3‐D fault model of the active structures involved in the sequence and those neighboring to them, benefiting of a large geological and seismological data set; (b) the implementation of the generated 3‐D fault model in a FE environment, by exploiting the elastic dislocation theory and considering the curved fault geometry and the crustal heterogeneities information; and (c) the optimization of the seismogenic crustal blocks model parameters in order to reproduce the geodetic measurements. We show that our modeling approach allows us to well reproduce the coseismic surface displacements, including their significant asymmetric pattern, as shown by the very good fit between the modeled ground deformations and the geodetic measurements. Moreover, a comparative analysis between our FE model results and those obtained by considering a classical analytical (Okada) model, for both the surface displacements and the Coulomb stress changes, has been performed. Our model permits to investigate the coseismic stress and strain field changes relevant to the investigated volume and their relationships with the surrounding geological structures; moreover, it highlights the very good correlation with the seismicity spatial distribution. The retrieved stress field changes show different maxima: (a) at few kilometers depth, within the main event surface rupture zone; (b) at depths of 5–9 km in correspondence of main event hypocentral area, along the SW dipping Paganica Fault System (PFS); and (c) at depths of 12–14 km, in correspondence of the largest aftershock hypocentral area, along a steep segment of an underlying east dipping basal detachment. Moreover, the main event hypocenter is localized in a region of high‐gradient strain field changes, while a deeper volumetric dilatation lobe involves the largest aftershock zone. From these findings, we argue that the AQE hanging wall downward movement along the steep portion of PFS might have been modulated by the underlying basal detachment; on the other hand, the coseismic eastward motion of the PFS footwall might have triggered further slip on the OS, thus releasing the largest aftershock on an independent source. The retrieved stress and strain field changes, which support the active role of the OS, have been also validated through a comparative analysis with those obtained from independent geological, seismological, and GPS measurements. Key Points: We investigate the stress and strain changes due to the L'Aquila 2009 earthquake and its main aftershock simulating the blocks kinematic We generate the fault model of the structures involved in the sequence by exploiting all available geological/seismological information The proposed FE model takes into account the 3‐D crustal heterogeneities, the complexity, and the curvature of the investigated fault system